Locating Gendered Resistance: Interethnic Conflict, Environmental Disaster, and Feminist Leadership in Sri Lanka - Allison Donine (European Scientific Journal, ESJ, 2016)
In geographically vulnerable and politically unstable regions such as Sri Lanka, I argue that linking natural hazards and climate-induced disasters to existing social problems is more pressing than ever. In the case of the 2004 Boxing Day tsunami, it was impossible to dissociate the two. This paper examines the following questions: Within the geo-political context of Sri Lanka, how does trauma (human-made or environmental) produce resistance to patriarchal traditions in communities along gender lines? What gaps do women-led groups and coalitions fill in responding to the needs of women in conflict and post-disaster landscapes? And how has the public participation of women in armed conflict and coalitions provided space for transgressive agency to redefine traditional expectations? I argue that a greater understanding of the ways in which women are resisting their construction as partial citizens can provide insight to their strength and role in shaping their personal identities as well as that of the state. Looking though the lens of distress, in conflict and environmental disaster, this paper explores how women have transformed moments of victimization into opportunities for resistance and agency.